A Virtual Morris Water Maze to Study Neurodegenarative Disorders - Roth, Daniel; Purps, Christian Felix; Neumann, Wolf Julian (Adjunct Proceedings of the 2020 IEEE International Symposium on Mixed and Augmented Reality, ISMAR-Adjunct 2020, 2020)
Navigation is a crucial cognitive skill that allows humans and animals to move from one place to another without getting lost. In neurological patients this skill can be impaired, when neural structures that form the brain networks important for spatial learning and navigation are impaired. Thus, spatial navigation represents an important measure of cognitive health that is impossible to test in a clinical examination, due to lack of space in examination rooms. Consequently, spatial navigation is largely neglected in the clinical assessment of neurological, neurosurgical and psychiatric patients. Virtual reality represents a unique opportunity to develop a systematic assessment of spatial navigation for diagnosis and therapeutic monitoring of millions of patients presenting with cognitive decline in the clinical routine. Therefore, we have adapted a classical spatial navigation paradigm that was developed for animal research, the "Morris Water Maze"as an openly available Virtual Reality (VR) application, that allows objective quantification of navigational skills in humans. This tool may be used in the future to aid the assessment of the human navigation system in health and neurological disease.
CRIS-Team Scopus Importer:2021-03-29
Keywords: HCI design and evaluation methods; Human computer interaction (HCI); Human-centered computing; Human-centered computing; Visualization; Visualization design and evaluation methods